2005
DOI: 10.1016/j.npep.2004.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Galanin receptors in the rat gastrointestinal tract

Abstract: Galanin functions are mediated by three distinct G-protein-coupled receptors, galanin receptor 1 (GalR1), GalR2 and GalR3, which activate different intracellular signaling pathways. Here, we quantified mRNA levels of GalR1, GalR2 and GalR3 in the gastrointestinal tract using real time RT-PCR. GalR1 and GalR2 mRNAs were detected in all segments with the highest levels in the large intestine and stomach, respectively. GalR3 mRNA levels were quite low and mostly confined to the colon. We also investigated the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 12 publications
2
24
2
Order By: Relevance
“…Galanin encoded by GAL is a neuroendocrine peptide, which is widely expressed in the central and peripheral nervous systems and also the gastrointestinal tract . Additionally, galanin modulates transmitter release from myenteric neurons via inhibition of voltage‐dependent calcium channels mediated by G‐protein‐coupled receptors . A recent genomewide study suggested GAL as a candidate for HSCR due to the reduced level of GAL expression in HSCR group compared with control group, and our results further supported this opinion.…”
Section: Discussionsupporting
confidence: 86%
“…Galanin encoded by GAL is a neuroendocrine peptide, which is widely expressed in the central and peripheral nervous systems and also the gastrointestinal tract . Additionally, galanin modulates transmitter release from myenteric neurons via inhibition of voltage‐dependent calcium channels mediated by G‐protein‐coupled receptors . A recent genomewide study suggested GAL as a candidate for HSCR due to the reduced level of GAL expression in HSCR group compared with control group, and our results further supported this opinion.…”
Section: Discussionsupporting
confidence: 86%
“…Expression of β‐actin (an endogenous internal control gene) was measured in parallel for every sample, and the data obtained for μOR, TNF‐α, and IL‐10 were normalized to those of the β‐actin. Relative quantities (RQ) of mRNA were analyzed using the comparative threshold cycle (Ct) method (Livak and Schmittgen,2001; Anselmi et al,2005).…”
Section: Methodsmentioning
confidence: 99%
“…(1) Brown et al, 1999; (2) Rohwedder et al, 2015; (3) Mercer et al, 2011; (4) Schoofs et al, 1993; (5) Siviter et al, 2000; (6) Nässel et al, 1998; (7) Holzer and Holzer-Petsche, 1997; (8) Hökfelt et al, 2001; (9) Coast et al, 2001; (10) Johnson et al, 2005; (11) Brugge et al, 2008; (12) LaJeunesse et al, 2010; (13) Vanderveken and O'Donnell, 2014; (14) Sternini, 1991; (15) Kendig et al, 2014; (16) Rattan and Tamura, 1998; (17) Anselmi et al, 2005; (18) Kaminski et al, 2002; (19) Veenstra, 2009; (20) Corleto, 2010; (21) Farhan et al, 2013; (22) Veenstra and Ida, 2014; (23) Ren et al, 2015; (24) Sano et al, 2015; (25) Takizawa et al, 2005; (26) Sterkel et al, 2012; (27) Chen et al, 2015; (28) Carlsson et al, 2013; (29) Slade and Staveley, 2016; (30) Bhatt and Horodyski, 1999; (31) Duve et al, 2000; (32) Rankin et al, 2005; (33) Audsley et al, 2008; (34) Heinonen et al, 2008; (35) Duve et al, 1994; (36) Audsley and Weaver, 2009; (37) Dockray, 2009.…”
Section: Figurementioning
confidence: 99%